Playing bit parts in Shakespeare - Mahood, M. M. (Molly Maureen) (Routledge, 2002)
Playing Bit Parts in Shakespeare is a unique survey of the small supporting roles - such as foils, feeds, attendants and messengers - that feature in Shakespeare's plays. Exploring such issues as how bit players should conduct themselves within a scene, and how blank verse or prose may be spoken to bring out the complexities of character-definition, Playing Bit Parts in Shakespeare brings a wealth of insights to the dynamic of scenic construction in Shakespeare's dramaturgy. M.M. Mahood explores the different functions of minimal characters, from clearing the stage to epi.